SOSIALISASI TENTANG MEMBANGUN GENERASI CAKAP LITERASI KEUANGAN DAN TEKNOLOGI PENDIDIKAN ANAK USIA DINI DI DESA SEMPU, KECAMATAN ANDONG, KABUPATEN BOYOLALI - Elina Intan Apriliani; Sukari (Migunani Nusantara: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve financial and technological literacy among early childhood students in Sempu Village, Andong District, Boyolali Regency. The activity was motivated by the low understanding of parents and educators regarding the importance of introducing financial and technological concepts from an early age. The method used included four stages: preparation, socialization, training, and mentoring, with a participatory approach. The results showed a significant improvement in parents’ and educators’ understanding of financial and technological literacy after the program. Children demonstrated great enthusiasm in learning basic financial concepts through game-based learning and storytelling, and they began to use digital learning media responsibly. This program had a positive impact on developing frugal habits, simple financial responsibility, and appropriate technology use. Thus, this activity successfully raised community awareness of the importance of preparing financially and technologically literate generations from early childhood.